PROBLEMS RELATED TO PEDAGOGICAL SUPPORT SYSTEM OF CHILDREN WITH HEARING IMPAIRMENT OR DISORDERS IN REPUBLIC OF ARMENIA (World Science, 2020)
In this article distinctive features related to the characteristic of children with hearing disorders due to story perception, teachers’ awareness level of research results related to mentioned problems, and some cultivated and justified approaches are presented. All researches are implemented in Republic of Armenian Tigranyan No 14 special school.